2016
DOI: 10.17507/tpls.0601.17
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ Attitudes toward Writing Instruction Based on Critical Language Awareness

Abstract: Abstract-The present study sought to investigate the attitudes of upper-intermediate EFL female learners toward writing instruction based on critical language awareness (CLA). Sixteen participants were selected based on their performance on a quick placement test (QPT) and a writing task. Three instruments namely, QPT, a researchers made opinionnaire and semi-structured interview were used to elicit the data. The findings of the opinionnaire and semi-structured interview revealed an overall positive attitude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(14 reference statements)
1
1
0
1
Order By: Relevance
“…This finding is in line with Ismail and Albakri (2012), Fageeh and Mekheimer (2013), Said et al (2013), andChang et al (2021) who reported that E-learning would help students to have a positive attitude towards the writing skills. A wide range of other studies including Tahriri et al (2016), Setyowati andSukmawan (2016), andKazemi Malekmahmudi andKazemi Malekmahmudi (2018) reported similar results in a face-to-face environment. However, Akhtar et al (2020) findings differed from those of the current study as the majority of students experienced a moderate level of anxiety throughout the E-learning course.…”
Section: Writing Anxiety and Writing Attitude Levelsupporting
confidence: 64%
“…This finding is in line with Ismail and Albakri (2012), Fageeh and Mekheimer (2013), Said et al (2013), andChang et al (2021) who reported that E-learning would help students to have a positive attitude towards the writing skills. A wide range of other studies including Tahriri et al (2016), Setyowati andSukmawan (2016), andKazemi Malekmahmudi andKazemi Malekmahmudi (2018) reported similar results in a face-to-face environment. However, Akhtar et al (2020) findings differed from those of the current study as the majority of students experienced a moderate level of anxiety throughout the E-learning course.…”
Section: Writing Anxiety and Writing Attitude Levelsupporting
confidence: 64%
“…In line with the results of the present study, Akkaya and Susar Kirmizi (2010) who investigated the relationship between attitudes to reading and time appointed to writing in primary education, it can be expressed that there is a positive important relationship between attitudes to writing and time appointed to writing. Similarly, Tahriri et al (2016) showed an overall positive attitude towards critical language awareness (CLA-based) writing class. On the other hand, Setyowati and Sukmawan's (2016) study concluded that writing is difficult and stressful for students; however, they have a moderate attitude towards writing.…”
Section: Resultsmentioning
confidence: 99%
“…El uso de la tecnología juega un papel fundamental en la mejora de la enseñanza y el aprendizaje del inglés como lengua extranjera, especialmente en áreas como la comprensión auditiva, la comprensión lectora y la escritura (Tahriri et al, 2016). Los estudiantes que participan en actividades de aprendizaje que integran tecnologías demuestran un alto rendimiento en la adquisición del idioma y perciben el aprendizaje como más interactivo y dinámico.…”
Section: Introductionunclassified